A agenda 2030 no governo do estado do Maranhão: iniciativas, programas e ações para a consecução dos objetivos de desenvolvimento sustentável - SOUSA, Iorrana Soares (2022)
One of the most recent initiatives to lead the world on a path of effective sustainability was adopted by world leaders at the headquarters of the United Nations (UN) in 2015. The document entitled “Transforming Our World: The 2030 Agenda for Sustainable Development” it is an ambitious and challenging proposal aimed at human beings, the planet, universal peace, respect, freedom, the eradication of poverty and the achievement of peace and prosperity. The 2030 Agenda has 17 Sustainable Development Goals (SDGs), 169 targets and 232 indicators to be achieved by 2030. Given the complexity of the Agenda and the challenge of implementing the 17 SDGs, the present study proposed to verify the initiatives, programs and actions that the Government of the State of Maranhão has been carrying out to achieve these goals. This dissertation, characterized as a case study, adopted bibliographic research, documental research and interviews to achieve the proposed objectives. Finally, it was found that the State of Maranhão formally adhered to the 2030 Agenda and adopts the SDGs in the existing planning instruments. However, actions such as setting goals, formulating indicators for monitoring and evaluating this Agenda lack implementation. As well as initiatives to further disseminate the SDGs within the State of Maranhão.